Grand Design and Economic Analysis of Solar-Wind Hybrid Renewable Energy Systems in MSTP Jepara - Denis Denis; Jaka Windarta; Vicky Prasetia; Gladys Datita Nathania; Richad Juven Hariara; Ahmad Arif Razaqi (P3M Politeknik Negeri Cilacap, 2024)
Marine Science Techno Park (MSTP) Jepara is a center of technology implementation aimed to encourage community economy development in the maritime sector. At present, Marine Science Techno Park (MSTP) Jepara’s electrical energy source is supplied by Perusahaan Listrik Negara (PLN), with coal-powered steam turbine generators as the main source of electrical energy generation. Therefore, a cleaner and more sustainable means of electrical energy generation is needed to fulfill the high energy demand. With this in mind, Universitas Diponegoro, as the proposer, in collaboration with MSTP Jepara, as the recipient, proposes the initiation of Hybrid Renewable Energy Systems (HRES) Power Plant construction as a way of obtaining an environmentally friendly and sustainable source of energy in this research as well as addressing the issues in the previous HRES simulations and implementations. This article will discuss various scenarios, their feasibility for implementation, and the economic returns gained from HRES installation on-site.